Screening of novel indole steroids as cytochrome P450 substrates in silico - Panada Ян U.; Faletrov, Yaroslav V.; Frolova, Nina S.; Shkumatov, Vladimir M. (Journal of the Belarusian State University. Chemistry, 2018)
In this work we describe the modeling of interactions between indole steroids and steroidogenic cytochromes P450. The highest possible affinity is expected of enzymes involved in cholesterol transformation (i. e. CYP3A4, CYP7A1, CYP11A1). In case of pregnane and estrane-converting proteins a decrease in the binding energy of synthetic steroids is found. The variations in affinity are explained in terms of structural difference. These calculations imply that indole steroids are most likely to be hydroxylated at positions 4 and 7 as well as interfere with CYP17A1 activity by heme coordination.